2009
DOI: 10.1016/j.ejcts.2008.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Choice of conduits for coronary artery bypass grafting: craft or science?

Abstract: Long-term patency of a bypass graft is an important determinant in reducing morbidity and increasing survival after coronary bypass surgery. The purpose of this review is to analyse factors contributing to improved outcomes of commonly used conduits. Progress has been limited by the lack of uniform definitions of graft failure and development of appropriate statistical models. Evolving techniques for assessing patency at more frequent intervals has provided insight into the time and sites of early disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 103 publications
0
46
0
3
Order By: Relevance
“…The arterial wall structure, comparable diameter, low-risk of harvesting site complications, and longterm preserved flow-mediated vasodilatation are perceived advantages of RA over the great saphenous vein (GSV) (ref. 5,6 ). Although, a number of observational studies have demonstrated the superiority of RA in terms of better patency and clinical outcome, randomized trials suggested only better angiographic results of RA in 1-year and 5-year follow-up with no difference in clinical outcome [5][6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arterial wall structure, comparable diameter, low-risk of harvesting site complications, and longterm preserved flow-mediated vasodilatation are perceived advantages of RA over the great saphenous vein (GSV) (ref. 5,6 ). Although, a number of observational studies have demonstrated the superiority of RA in terms of better patency and clinical outcome, randomized trials suggested only better angiographic results of RA in 1-year and 5-year follow-up with no difference in clinical outcome [5][6][7][8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 ). Although, a number of observational studies have demonstrated the superiority of RA in terms of better patency and clinical outcome, randomized trials suggested only better angiographic results of RA in 1-year and 5-year follow-up with no difference in clinical outcome [5][6][7][8][9][10][11] . Moreover, dealing with less tight coronary lesions (<80%), particularly in the right coronary artery territory, and with the group of patients 70+, use of RA did not carry any benefit of importance over GSV (ref.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,15 Many factors determine graft patency, including patient characteristics, target vessel and conduit selection, 18 surgical technique, 18 postoperative medical therapy, and risk factor management. 19 The endothelium modulates vascular reactivity via a number of factors that include nitric oxide, endothelium-derived hyperpolarizing factor, and endothelin and also has antiproliferative and antithrombotic properties. 20 In our study, endothelial function was tested with acetylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike saphenous vein graft, which has a median patency of 7 years, more than 90% of IMA grafts are patent at 15 years [21]. This in part is attributable to its endothelial function.…”
Section: Discussionmentioning
confidence: 99%